Cognitive Skills of Employees from the Pharmaceutical Field - Sălceanu, Claudia; Caraion, Raluca-Simona (Technium Social Sciences Journal, 2022)
<span style="font-size: 11.0pt; mso-bidi-font-size: 10.0pt; font-family: 'Times',serif; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Over time, the specialised literature had an increased interest regarding the study of intelligence, cognitive abilities, and about the way these two abilities correlate amongst them. A sample of 63 pharmacists, aged between 25 and 45 years old, from Constanta County, was assessed with the cognitive skills tests from Cognitrom Assessment System (CAS++). Our study aimed at (1) identifying the level of cognitive skills that employees in the pharmaceutical field have; (2) identifying differences according to age in terms of cognitive abilities; and (3) identifying the relationships between cognitive abilities. One set of hypotheses assumed relationships between inductive analytical reasoning and analogical transfer, and between vocabulary and analogical transfer. Another set of hypotheses assumed the existence of differences between young pharmacists and adult pharmacists regarding analogical verbal transfer, decision-making capacity, inductive analytical reasoning, syntax, and vocabulary-synonyms. Results confirmed the correlational hypotheses and the difference regarding the vocabulary-synonyms variable but infirmed all the other hypotheses. Results are discussed in the context of the importance of cognitive skills for the pharmaceutical field, especially in the COVID-19 pandemic context.